Effects of supplementing organic‘ and inorganic‘based selenium with vitamin e on intestinal histomorphology, caecal bacterial proliferation, and short‘chain fatty acid profile in layer hens - Zainudin, N.N.; Hemly, N.I.M.; Muhammad, A.I.; Nayan, N.; Samsudin, A.A. (Springer, 2023)
The effects of supplementing different dietary selenium (Se) sources on intestinal histomorphology, caecal bacterial proliferation, and caecum short-chain fatty acid in layer chickens were studied. A total of 120 of 54-week-old Lohman Brown Classic laying hens were subjected to four dietary treatments: control group with no Se supplementation (T1), 0.3 mg/kg of sodium selenite (T2), 0.3 mg/kg of selenium yeast (T3), and 0.3 mg/kg of bacterial Se (Stenotrophomonas maltophilia, ADS18) (T4). All treatments were also supplemented with 250 mg/kg of vitamin E. Results showed significant (p < 0.05) higher villus height in different small intestine parts in hens fed with diets containing organic Se sources (T3 and T4), as compared to inorganic sources (T2) and control (T1). A greater crypt depth was observed for the T1 group, as compared to T3 and T4 groups. The total bacterial populations of Bifidobacteria spp. and Lactobacilli spp. were significantly increased (p < 0.05), and escherichia coli population was significantly decreased (p < 0.05) in T3 and T4 groups. No effect on the total caecal short-chain fatty acid (SCFAs) content was observed. However, there was a significant increase (21.5) of the butyric acid content in T4 group. In conclusion, organic Se supplementation, particularly bacterial organic Se, enhances intestinal histomorphology, increases the beneficial caecal bacterial proliferation, and increases butyric acid content.